Transcription Factors FHY3 and FAR1 Regulate Light-Induced CIRCADIAN CLOCK ASSOCIATED1 Gene Expression in Arabidopsis. Issue 5 (9th March 2020) - Liu, Yang; Ma, Mengdi; Li, Gang; Yuan, Li; Xie, Yurong; Wei, Hongbin; Ma, Xiaojing; Li, Quanquan; Devlin, Paul F.; Xu, Xiaodong; Wang, Haiyang
Abstract : Members of the photosensory-signaling pathway orchestrate the expression of the circadian clock gene CCA1 to regulate plant responses to daily changes in the light environment. Abstract: The circadian clock provides a time-keeping mechanism that synchronizes various biological activities with the surrounding environment. Arabidopsis ( Arabidopsis thaliana ) CIRCADIAN CLOCK ASSOCIATED1 ( CCA1 ), encoding a MYB-related transcription factor, is a key component of the core oscillator of the circadian clock, with peak expression in the morning. The molecular mechanisms regulating the light induction and rhythmic expression of CCA1 remain elusive. In this study, we show that two phytochrome signaling proteins, FAR-RED ELONGATED HYPOCOTYL3 (FHY3) and its paralog FAR-RED IMPAIRED RESPONSE1 (FAR1), are essential for the light-induced expression of CCA1 . FHY3 and FAR1 directly bind to the CCA1 promoter and activate its expression, whereas PHYTOCHROME INTERACTING FACTOR5 (PIF5) directly binds to its promoter and represses its expression. Furthermore, PIF5 and TIMING OF CAB EXPRESSION1 physically interact with FHY3 and FAR1 to repress their transcriptional activation activity on CCA1 expression. These findings demonstrate that the photosensory-signaling pathway integrates with circadian oscillators to orchestrate clock gene expression. This mechanism might form the molecular basis of the regulation of the clock system by light in response to daily changes in the light environment, thus increasing plant fitness.